Loss-of-function mutations in cardiac ryanodine receptor channel cause various types of arrhythmias including long QT syndrome. Issue 3 (18th October 2021) - Hirose, Sayako; Murayama, Takashi; Tetsuo, Naoyuki; Hoshiai, Minako; Kise, Hiroaki; Yoshinaga, Masao; Aoki, Hisaaki; Fukuyama, Megumi; Wuriyanghai, Yimin; Wada, Yuko; Kato, Koichi; Makiyama, Takeru; et al.
Abstract: Aims: Gain-of-function mutations in RYR2, encoding the cardiac ryanodine receptor channel (RyR2), cause catecholaminergic polymorphic ventricular tachycardia (CPVT). Whereas, genotype–phenotype correlations of loss-of-function mutations remains unknown, due to a small number of analysed mutations. In this study, we aimed to investigate their genotype–phenotype correlations in patients with loss-of-function RYR2 mutations. Methods and results: We performed targeted gene sequencing for 710 probands younger than 16-year-old with inherited primary arrhythmia syndromes (IPAS). RYR2 mutations were identified in 63 probands, and 3 probands displayed clinical features different from CPVT. A proband with p.E4146D developed ventricular fibrillation (VF) and QT prolongation whereas that with p.S4168P showed QT prolongation and bradycardia. Another proband with p.S4938F showed short-coupled variant of torsade de pointes (scTdP). To evaluate the functional alterations in these three mutant RyR2s and p.K4594Q previously reported in a long QT syndrome (LQTS), we measured Ca 2+ signals in HEK293 cells and HL-1 cardiomyocytes as well as Ca 2+ -dependent [ 3 H]ryanodine binding. All mutant RyR2s demonstrated a reduced Ca 2+ release, an increased endoplasmic reticulum Ca 2+, and a reduced [ 3 H]ryanodine binding, indicating loss-of-functions. In HL-1 cells, the exogenous expression of S4168P and K4594Q reduced amplitude of Ca 2+ transients without inducing Ca 2+ waves, whereas that of E4146D and S4938F evoked frequent localized Ca 2+ waves. Conclusion: Loss-of-function RYR2 mutations may be implicated in various types of arrhythmias including LQTS, VF, and scTdP, depending on alteration of the channel activity. Search of RYR2 mutations in IPAS patients clinically different from CPVT will be a useful strategy to effectively discover loss-of-function RYR2 mutations. Graphical Abstract: